Strategi Penyiapan Aparat Komando Kewilayahan (Kowil) dalam Operasi Teritorial Pada Operasi Gabungan TNI di Wilayah Kodam II/Sriwijaya - Arif, Abdillah (Dinasti Research, 2024)
This research aims to analyze the strategy for preparing Territorial Command Apparatus (Kowil) in territorial operations carried out by the Indonesian National Armed Forces (TNI) in the Kodam II/Sriwijaya region. The research employs a qualitative method with a case study approach, involving in-depth interviews, observations, and document analysis. The findings indicate that the strategies implemented include intensive training In the field of Territorial (Devotion to the Indonesian Armed Forces (Bhakti TNI), Social Communication (Komsos), and Regional Defense Training (Binwanwil)), enhancement of inter-agency cooperation, and the use of information technology to support communication and coordination. Additionally, community participation is considered crucial for the success of territorial operations. This study provides recommendations for further development in preparing Kowil apparatus in order to optimize their tasks and functions.